Efektivitas Penerapan Model Modifikasi Tingkah Laku (Behavioral Modification) Terhadap Peningkatan Hasil Belajar Fisika Peserta Didik - Rafiqah, Rafiqah; Suhardiman, Suhardiman; Fauziah, Fauziah (Al-Khazini, 2021)
This research is a Quasi Experimentalstudy which aims to describe the increase in student learning outcomes before and after being taught using a behavior modification model and to determine the effectiveness of behavior modification models on increasing student competitiveness. The researchdesign used was Time Series Design. The population in this study were all class X MIA 1 SMAN 1 Woha, totaling 36 people. The research sample consisted of 36 people. Sampling was carried out by means of convenience sampling. The results of descriptive research indicate that the average value of physics learning outcomes of students who before being taught uses a behavior modification model (Behavioral Modification). At the first meeting it was 51.67, at the second meeting it was 52.77, at the third meeting it was 56.28, and the three scores were in the sufficient category. While the average value of students' physics learning outcomes after being taught using a behavior modification model (Behavioral Modification). At the fourth meeting it was 80.83, at the fifth meeting it was 85.36 and at the sixth meeting it was 88.05. The three values are in the good category. Furthermore, the data obtained using the Wilcoxon Matched Pairs test obtained a significant value of 0.00 <0.05. So that there are significant differences in student learning outcomes before and after being taught with a behavior modification model.